Дипломатичні зносини Запорозької Нової Січі з Кримським ханством. (Zaporizhzhia Historical Review, 2021)
The author investigates the problem of diplomatic contacts between Crimean Khanate and Zaporizhzhyan Cossackhood in times of the New Sich existence. It is demonstrated that frequent change of Khans and Kosh Otamans, the intensification of Tzar’s administrative control upon the foreign politics of Zaporizhzhya, the worsening of Russian-Crimean and Russian-Turkish relations had hampered the establishment of mutual diplomatic relationship and therefore prevented the realization of potential of Zaporizhzhyan-Tatar diplomacy.